Locally Homogeneous Holomorphic Geometric Structures on Projective Varieties - Biswas, Indranil; McKay, Benjamin (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
For any smooth projective variety with a holomorphic locally homogeneous structure modelled on a homogeneous algebraic variety, we determine all the subvarieties of it that develop to the model.